Antiproliferation effect of imatinib mesylate on MCF7, T-47D tumorigenic and MCF 10A nontumorigenic breast cell lines via PDGFR-β, PDGF-BB, c-Kit and SCF genes - Kadivar A; Kamalidehghan B; Akbari Javar H; Karimi B; Sedghi R; MI Noordin (Dove Medical Press, 2017)
Ali Kadivar,1 Behnam Kamalidehghan,1 Hamid Akbari Javar,2 Benyamin Karimi,3 Reihaneh Sedghi,4 Mohamed Ibrahim Noordin1 1Department of Pharmacy, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia; 2Department of Pharmaceutics, Faculty of Pharmacy, Tehran University of Medical Sciences (TUMS), Tehran, Iran; 3Department of Pharmacology, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia; 4Faculty of Medicine, Shiraz University of Medical Sciences (SUMS), Shiraz, Iran Abstract: Recent cancer molecular therapies are targeting main functional molecules to control applicable process of cancer cells. Attractive targets are established by receptor tyrosine kinases, such as platelet-derived growth factor receptors (PDGFRs) and c-Kit as mostly irregular signaling, which is due to either over expression or mutation that is associated with tumorigenesis and cell proliferation. Imatinib mesylate is a selective inhibitor of receptor tyrosine kinase, including PDGFR-β and c-Kit. In this research, we studied how imatinib mesylate would exert effect on MCF7 and T-47D breast cancer and MCF 10A epithelial cell lines, the gene and protein expression of PDGFR-β, c-Kit and their relevant ligands platelet-derived growth factor (PDGF)-BB and stem cell factor (SCF). The MTS assay was conducted in therapeutic relevant concentration of 2–10 µM for 96, 120 and 144 h treatment. In addition, apoptosis induction and cytostatic activity of imatinib mesylate were investigated with the terminal deoxynucleotidyl transferase dUTP nick end labeling TUNEL and cell cycle assays, respectively, in a time-dependent manner. Comparative real-time PCR and Western blot analysis were conducted to evaluate the expression and regulation of imatinib target genes and proteins. Our finding revealed that imatinib mesylate antiproliferation effect, apoptosis induction and cytostatic activity were significantly higher in breast cancer cell lines compared to MCF 10A. This effect might be due to the expression of PDGFR-β, PDGF-BB, c-Kit and SCF, which was expressed by all examined cell lines, except the T-47D cell line which was not expressed c-Kit. However, examined gene and proteins expressed more in cancer cell lines. Therefore, imatinib mesylate was more effective on them. It is concluded that imatinib has at least two potential targets in both examined breast cancer cell lines and can be a promising drug for targeted therapy to treat breast cancer. Keywords: Gleevec, breast cancer, normal breast cell line, tyrosine kinase receptor, protein expression, comparative real-time PCR, cell cycle analysis, cell cycle arrest, cytostatic activity